PENGARUH KOMPOSISI PENGELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi pada Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia) - Meyzia Irestia Putri; Mujino Mujino; Risal Rinofah (Jurnal Fokus Manajemen Bisnis, 2020)
This study aims to examine the effect of the composition of company managers on financial performance. The composition of the company management is proxied by using the number of independent commissioners, the board of commissioners, and the board of directors. The company's financial performance is measured by profitability ratios, namely Return On Investment (ROI). The population in this study are companies that are included in the State Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (BEI) in 2010-2018.The sample selection technique used purposive sampling method. Based on the criteria that have been determined, 8 companies chosen as sample. The type of data used are secondary data in the form of annual reports and financial statements. Data analysis technique used multiple linear regression analysis.The results of this study showed that simultaneously, independent commissioner, board of commissioner, and board of directors have a significant effect on ROI. Partially, independent commissioner, audit committee, board of commissioner, and board of directors has positive and significant effect on ROI. While another Good Corporate Governance proxy, which are the audit committee and board of directorsÂ  have a positive effect but not significant on ROI.